DETERMINANTS OF STOCK MARKET PERFORMANCE IN BANGLADESH - Mohammad Saleh Jahur; S. M. Nasrul Quadir; Mohammad Aktaruzzaman Khan (Indonesian Management and Accounting Research, 2014)
Stock market influences economic activity through the creation of liquidity of capital investment. Liquid stock markets make investment less risky and more investment. Stock market in Bangladesh is characterized by frequent changes in regulations, low market sizes-market capital & turnover, lowest number of financial products, low contribution to national exchequer, influx of large number investors without relevant knowledge, and expertise. Besides, Bangladesh stock market experienced different problems-regulatory failure, unethical and ill objective oriented behavior of market participants, lack of due diligence, and manipulation. So, market cannot perform well. In view of this, the present study has been undertaken aiming at identifying determinants of stock market in Bangladesh. The study has collected data from the secondary sources and analyzed the data collected by applying some descriptive measures, and linear regression model. The study has found that the stock market of the country is characterized by different features such as low size, low liquidity, low depth, acute fund crisis and so on. The study has also found from linear regression analysis that all macro-economic variables such as CPI, Interest Rate, IR, and ER have significant impact on the stock market performance. Finally, the paper concludes with some pragmatic policy measures such as sound macroeconomic policy for monitoring interest rate and exchange rate movement.Keywords : Stock Market, Liquidity, Performance, Macro-economy, and investment